Foreword - Kosyan, Aram (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
Urartian prosopography until present remains one of the poorly studied directions of Urartology, especially if one takes into account available linguistic data which testifies that Urartu was home to numerous ethnic groups whose linguistic affiliation still is a subject for special studies, not to mention possible foreign enclaves in different parts of the Empire, especially on its periphery. The present study offered by Dr. Yervand Grekyan, one of leading experts in Urartology, is the first attempt to gather all available onomastic and biographical data of individuals known so far from Urartian, Neo-Assyrian, Neo- and Late Babylonian texts and Achaemenid royal inscriptions. Thus, the study covers approximately 300 years, from the first half of the IX until the VI century BC. The catalogue presented in five Appendixes, includes three hundred names of individuals from Urartu and its neighbouring countries, as well as those, the inhabitants of Assyria, who are in some way related with Urartu, figuring in the sources either as ‘Urartians’ or bore ‘Urartian’ names. The etymological section presents the main discussion and aims to clarify the ethno-linguistic character of Urartu and its neighbours in the Armenian Highland. It goes without saying that the ‘Prosopography’ is a highly valuable contribution in Urartology that offers well-founded study based upon wide textual data coming from Urartu proper and neighbouring Near Eastern states.